PENGARUH METODE BERCERITA MENGGUNAKAN BUKU CERITA BERGAMBAR TERHADAP KETERAMPILAN BERBICARA ANAK USIA DINI DI KB NUR SUCI KABUPATEN PANGKEP - A Suci Rahmadani; Herman; Azizah Amal; Syamsuardi; Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims 1) to determine the description of the speaking skills of children aged 5-6 years in the control class before and after implementing the storytelling method using picture story books at the Nur Suci KB, Pangkep Regency. 2) To find out the description of the speaking skills of children aged 5-6 years in the experimental class before and after implementing the storytelling method using picture story books at KB Nur Suci Pangkep Regency, 3) To find out the differences in speaking skills between the control class and the experimental class after being given method treatment telling stories using picture story books for children aged 5-6 years at KB Nur Suci Pangkep Regency. Research design using Quasi Experimental Design. The data collection techniques used in this research are observation, tests and documentation. The subjects in this study were 13 people in the control group and 13 people in the experimental group. The results of the research show that there is a significant influence in the application of the storytelling method using picture story books on the speaking skills of children in group B at KB Nur Suci Pangkep Regency, with the results showing that the value obtained from the experimental group obtained an Asymp Sig (2-tailed) value of 0.000 <0.05.